Synthesis of Functionalized Fused-Ring Heterocycles from Tautomers of 2-(Thiazole, Oxazole, Benzothiazole, and Benzoxazole)-1-phenylethenols and 1,3-Diacid Chlorides or N-(Chlorocarbonyl) Isocyanate - De Silva, Hondamuni I.; Chatterjee, Sabornie; Henry, William P.; Pittman, Charles U., Jr. (Synthesis, 2012)
2-Methylthiazole, 2,4,5-trimethylthiazole, 2,4,5-trimethyloxazole, 2-methylbenzothiazole, and 2-methylbenzoxazole were each reacted with benzoyl chloride in acetonitrile–triethylamine to generate (Z)-2-(heterocyclic)-1-phenylvinyl benzoates. Base hydrolysis of these vinyl benzoates formed (Z)-2-(heterocyclic)-1-phenylethenols, which exist in both keto and enol tautomeric forms. These tautomers were used as starting materials for fused-ring heterocycle syntheses. Reactions with 2,2-dialkyl-1,3-diacid chlorides in acetonitrile–triethylamine afforded their corresponding 5,6-ring-fused 8-benzoyl-6,6-dialkyl-6H-thiazolo-, 8-benzoyl-2,3,6,6-tetramethyl-6H-thiazolo-, 8-benzoyl-2,3,6,6-tetramethyl-6H-oxazolo-, 4-benzoyl-2,2-dimethyl-1H-benzo[4,5]thiazolo-, and 4-benzoyl-2,2-dimethyl-1H-benzo[4,5]oxazolo[3,2,-a]pyridinedione derivatives. The 5,6,6-tri-ring fused species, 10-benzoyl-7,8-dihydropyrano[2,3-d]thiazolo[3,2-a]pyridin-5(6H)-one, was formed in the reaction of the tautomers of (Z)-1-phenyl-2-(thiazol-2-yl)ethenol with cyclobutane-1,1-dicarbonyl dichloride via a ring expansion after 5,6-ring fusion. Functionalized 5,6-ring-fused 8-benzoyl-6H-thiazolo- and 8-benzoyl-6H-oxazolo[3,2-f]pyrimidine-5,7-diones, and 4-benzoyl-1H-benzo[4,5]thiazolo- and 4-benzoyl-1H-benzo[4,5]oxazolo[3,2-c]pyrimidine-1,3(2H)-diones were also synthesized by reacting the (Z)-2-(heterocyclic)-1-phenylethenol tautomers with N-chlorocarbonyl isocyanate in THF–triethylamine.
Keywords: keto-enol tautomers; dielectrophiles; fused-ring heterocycles; nucleophilic attack; cyclocondensation